1986
DOI: 10.1136/bmj.293.6543.363
|View full text |Cite
|
Sign up to set email alerts
|

Does informed consent influence therapeutic outcome? A clinical trial of the hypnotic activity of placebo in patients admitted to hospital.

Abstract: To examine whether written informed consent might influence the results of clinical trials the effect of placebo when given with or without informed consent to patients suffering from insomnia was studied. The study was a single blind observer blinded trial, and patients were paired according to sex, age, and hospital environment. Randomisation assigned the first patient of each pair to the control group (without informed consent) or the group to give informed consent. Of the 56 patients, 26 refused to give in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…Two studies randomised 82 patients to “n of 1 trials” compared with standard practice—that is, randomised, double blind, multiple crossover comparisons of an active drug with a placebo in a single patient 9 10. One study (60 patients) measured spontaneously self reported side effects in patients who had or had not been informed that they were in an RCT 11. One study (227 patients) reported satisfaction among patients randomised to an RCT compared with patients randomised to a patient preference trial in which they had a choice of treatment 12.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies randomised 82 patients to “n of 1 trials” compared with standard practice—that is, randomised, double blind, multiple crossover comparisons of an active drug with a placebo in a single patient 9 10. One study (60 patients) measured spontaneously self reported side effects in patients who had or had not been informed that they were in an RCT 11. One study (227 patients) reported satisfaction among patients randomised to an RCT compared with patients randomised to a patient preference trial in which they had a choice of treatment 12.…”
Section: Resultsmentioning
confidence: 99%
“…Does the fact of asking for fully informed consent and providing the necessary information on which to base a decision, affect therapeutic outcome? Dahan et al 8 investigated this possibility in a clinical trial of the hypnotic activity of a placebo. Patients were paired and one of each pair was assigned to a control group where there was no informed consent.…”
Section: Informed Consent -Help or Hindrancementioning
confidence: 99%
“…On the other hand, it has been demonstrated that obtaining an informed consent per se affects the outcome of the clinical trial. Patients who were informed of the potential side effects were more likely to report such side effects or to withdraw from the study (Dahan et al, 1986). Such ®ndings were seen by some to support not seeking consent (Baum, 1986).…”
Section: The Null Hypothesismentioning
confidence: 95%